1991
DOI: 10.1111/j.1398-9995.1991.tb00585.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational asthma in bakeries caused by sensitivity to α‐amylase

Abstract: We report on a patient with asthma induced by occupational exposure to alpha-amylase derived from Aspergillus oryzae, which is a component of bread additives. A type I hypersensitivity to this enzyme was demonstrated by means of skin test, immunoassay for specific IgE, and immediate bronchial provocation test response to an alpha-amylase extract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Furthermore, the presence of atopy modified this response for a given exposure, and modeling suggests that work-related sensitization could be reduced to negligible levels when exposure to total inhalable dust in bakeries is reduced to below 0.5 mg/m 3 . Many studies in bakeries now demonstrate significant acquisition of sensitization to enzyme based flour improvers, and an association between sensitization and work-related symptoms [Brisman and Belin, 1991;Carmona et al, 1991;Houba et al, 1996;Elms et al, 2003a]. Certain of these data suggest that dual sensitization to wheat flour and at least one enzyme may be particularly important in determining workrelated symptoms.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the presence of atopy modified this response for a given exposure, and modeling suggests that work-related sensitization could be reduced to negligible levels when exposure to total inhalable dust in bakeries is reduced to below 0.5 mg/m 3 . Many studies in bakeries now demonstrate significant acquisition of sensitization to enzyme based flour improvers, and an association between sensitization and work-related symptoms [Brisman and Belin, 1991;Carmona et al, 1991;Houba et al, 1996;Elms et al, 2003a]. Certain of these data suggest that dual sensitization to wheat flour and at least one enzyme may be particularly important in determining workrelated symptoms.…”
Section: Introductionmentioning
confidence: 92%
“…Many of the enzymes used in the baking industry are Aspergillus-derived, such as cellulase, hemicellulase and fungal a-amylase, although the list of added enzymes has increased to include bacterial a-amylase, amyloglucosidase, glucoamylase and lipases. Recently, we demonstrated measurable levels of bacterial amylase and amyloglucosidase in bakeries [Elms et al, 2006], but much of the previous research has focused on fungal a-amylase, which has also been shown to be a potent sensitizer [Brisman and Belin, 1991;Carmona et al, 1991]. Whilst the majority of evidence therefore relates to fungal a-amylase, other less frequently used enzymes are also thought to cause ill health effects [Baur et al, 1988[Baur et al, , 1998Quirce et al, 1992;Merget et al, 2001;Elms et al, 2003b].…”
Section: Introductionmentioning
confidence: 94%
“…It is routinely added to baking flour (in amounts of milligrams per kg flour) to hasten the baking process and improve bread quality. Several individual case reports have been reported of baker's asthma caused by this starch cleaving enzyme in the absence of demonstrable reactivity to cereal allergens [Heyer, 1983;Baur et al, 1986;Birnbaum et al, 1988;Wüthrich and Baur, 1990;Bermejo et al, 1991;Blanco Carmona et al, 1991;Tarvainen et al, 1991b;Quirce et al, 1992;Valdivieso et al, 1994]. In other studies, 24-55% of bakers with respiratory symptoms attending medical services, were found to be sensitized to ␣-amylase [Baur et al, 1988[Baur et al, , 1989[Baur et al, , 1994aWüthrich and Baur, 1990].…”
Section: Fungal Amylasementioning
confidence: 99%
“…From the family of the carbohydrases, α-amylase of fungal origin was shown to be an important occupational allergen in the baking industry [40,41] that may induce both early and late reactions after inhalation in sensitized patients [42]. In vitro cultures of epithelial cells (A549) with a highly purified α-amylase shows the induction of interleukin (IL)-6 and IL-8 cytokines with maximum production at 25 µg/ml and morphologic changes (shrinking and shedding) of epithelial cells at levels above 200 µg/ml, indicating loss of cellular contacts (Fig.…”
Section: Factors In the Allergen Source That Might Facilitate Allergementioning
confidence: 99%